MiR‐374a promotes cell proliferation, migration and invasion by targeting SRCIN1 in gastric cancer. Issue 3 (29th December 2014) - Xu, Xinyun; Wang, Weijun; Su, Ning; Zhu, Xujun; Yao, Jun; Gao, Wenchao; Hu, Zhiqian; Sun, Yanping
Abstract : MicroRNAs (miRNAs) play a prominent role in gastric cancer (GC) initiation and progression. In this study, we found that miR‐374a expression was up‐regulated in human GC cell lines and tissues. Inhibition of miR‐374a suppressed GC cell proliferation, migration and invasion in vitro and slowed tumor growth in vivo. SRC kinase signaling inhibitor 1 (SRCIN1) was identified as a direct target of miR‐374a. Silencing of SRCIN1 significantly enhanced cell proliferation, migration and invasion, whereas SRCIN1 reintroduction partially abrogated the oncogenic effects of miR‐374a. Taken together, these findings suggest that miR‐374a functions as a candidate oncogene in GC by directly targeting SRCIN1. miR‐374a may therefore be useful as a promising therapeutic target for malignant GC. Abstract : miR‐374a expression is up‐regulated in human GC cell lines and tissues. miR‐374a inhibition suppresses GC cell proliferation, migration and invasion. miR‐374a inhibition suppresses tumorigenicity in nude mice. SRCIN1is a direct target of miR‐374a.